Learning from Ridhima Pandey : A Childist Ethics of Care for a Postpaternalist Era - Boje Mortensen, Therese (International Journal of Children's Rights, 2025)
When children exercise their right to political participation through climate activism and litigation, they demonstrate that an ethics of care is a core component of the postpaternalist era. Children’s ethics of care, however, is not only about care toward their immediate human relations, but also toward other species, the environment they live in and generations to come. They thereby develop the traditional feminist ethics of care into a childist version which takes seriously children’s experiences. While children themselves – as we speak – are performing a childist ethics of care, it is not yet theoretically formulated, and that is what the present article does. To exemplify, the article analyses nine-year-old Ridhima Pandey’s petition to India’s National Green Tribunal. The petition both demonstrates the components of a childist ethics of care in the context of the climate crisis, and real-life challenges and hopes for children who exercise rights within adultist structures.
Keywords: Child rights; Ethics of care; Childism; Postpaternalism; Climate litigation